Analisis Manfaat Pengembangan Organisasi di SD Negeri 17 Pakan Kurai di Kecamatan Guguak Panjang - Aldi (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to analyze the perspective of SDN 17 Pakan Kurai on the benefits of organizational development in improving the quality of education. The research used a qualitative descriptive approach with data collection techniques through interviews, observation, and document analysis. The findings reveal that organizational development has a positive impact on school management effectiveness, teacher job satisfaction, and the overall quality of learning. The study concludes that organizational development plays a key role in fostering adaptive, innovative, and quality-oriented educational institutions..